Effect of growth media on the MTT colorimetric assay in bacteria - Benov, Ludmil (PLoS One, 2019)
Reduction of tetrazolium salts to colored formazan products by metabolically active cells is widely used for assessment of cell viability. Among the tetrazolium compounds most commonly used is MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide]. Numerous studies about sites and mechanisms of cellular reduction of MTT, performed in mammalian cell cultures, have identified various parameters that affect formazan production and can lead to overestimation/underestimation of viable cells or effects of treatment. Irrespective of lack of such data for prokaryotic cells, the MTT assay is commonly used for microbiological studies, which often leads to contradictory results or misinterpretation of data. The aim of this study was to investigate how components of growth media and conditions of growth, affect formazan formation by microbial cells. Results showed that MTT reduction depended on the amino acid composition of the medium. Several amino acids potentiated formazan production by Gram-positive and Gram-negative bacteria, with histidine having the strongest effect. Results of this study demonstrate that data obtained with the MTT test should be interpreted with caution, particularly when different growth media are used or treatments affect metabolic pathways, and that evaluation of the reliability of the MTT assay under specific conditions should be performed, to avoid erroneous results. Performing the assay with cells suspend in glucose-supplemented buffer would eliminate the effects of metabolites and will limit cell division during incubation with MTT. Another critical element to be considered is the choice of a proper solvent for dissolution of formazan crystals.